Szelídgesztenye kéregrák (Cryphonectria parasitica) vizsgálata kocsánytalan tölgyeken a Lenti és Letenyei Erdészet területén - Tótiván Benjámin (2019)
In my thesis, I investigated Quercus species and Castanea sativa health condition with par-ticular regard to Crypphonectria parasitica infection on Castanea sativa and Quercus petra-ea in five forest stands in Tenke woods. I also tried to find connections between health condition, tree stock characteristics, dendrometric data and habitat endowments. During my examinations, I did a survey on the field, I collected samples from outwardly infected trunks. I isolated the present pathogens from the samples under laboratory conditions. I tested the compatibility of my C. parasitica samples and in the lab available hypovirulent strains. My results showed that the Castanea sativa health condition is very weak in this area. In those stands, which contain living chestnuts, a greater amount of game damage can notice, which condition promotes the spread of this disease. In case of the Quercus petraea, four of the five examined stands I could detected the C. parasitica infection. The infection appear as a weakness rather than a decaying regarding the diseased trees. In my investiga-tion, the chestnut blight could not be found on the Quercus cerris and Quercus robur.